Опасные факторы пожара на начальной стадии в смежном помещении в рамках интегральной модели - Kuz’mitskiy Валерий; Polevoda Иван; Osyaev Владимир (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The integral model equations have been presented which describe fire in the building consisting of several enclosures. The dynamic of fire dangerous factors at initial stage has been considered for the case of two enclosures. For the indoor adjacent to the enclosure in fire, the analytical dependencies for the dynamic of the gas medium changes has been obtained.